PENGARUH PENDEKATAN PROBLEM-BASED LEARNING (PBL) BERSTRATEGI MAKE-A MATCH TERHADAP KEMAMPUAN KONEKSI DAN DISPOSISI MATEMATIS - Rahayu, Isa Nuraisyah; Maulana, Maulana; Kurnia, Dadang (Jurnal Pena Ilmiah, 2019)
This research purpose to compare problem-based learning approach using make-a match and conventional approach in improving studentsâ€™ mathematical connection ability and mathematical disposition, and how is relation between mathematical connection ability and mathematical disposition. Quasi experimental method with the nonequivalent control group design was used in this research. All fifth graders of elementary school in Tanjungsari sub-district was population in this research, while the sample was taken from SD NegeriÂ Tanjungsari 1, class V-A as the control class, and class V-B as the experimental class. The non-test and test instrument was used in this research. Learning with problem-based learning approach using make-a match is significantly better than conventional learning in improving mathematical connection ability and mathematical disposition of student. There is a positive relationship between mathematical connection ability and mathematical disposition of students.